CHARACTERISTICS OF KWETIAU MATERIAL OF FORMULATION RICE FLOUR AND UWI FLOUR, TARO FLOUR AND KIMPUL FLOUR MODIFIED BY HEAT MOISTURE TREATMENT (HMT) - Ledy Purwandani, Erning Indrastuti, Muflihah Ramadhia & (Proceeding of International Congress, 2014)
The purpose of this study is to determine the effect of substitution uwi flour, taro flour, and kimpul flourmodified on rice flour that can produce the best characteristics of high resistant starch kwetiau. HMTmodification on the uwi/ keribang/ coconut yam (Dioscorea alata) flour, taro (Colocasia esculenta (L)Schott) flour and kimpul/ sarawak taro/ belitung taro (Xanthosoma sagittifolium (L) Schott) flourcharacteristics can be applied to the manufacture of kwetiau . The nature of the lack of appropriatenatural starch is expected to be improved by modification of starch is by Heat Moisture Treatment(HMT). HMT treatment is 20% and 30% water content with heating time 4, 6, 8, 10 hours at 80 Â° C. Theresults showed HMT modification effect on the water content and crystallinity of uwi flour, taro flour andkimpul flour.Keywords: Heat MoistureTreatment, Kimpul, Resistant Starch, Taro, Uwi.